2007
DOI: 10.1073/pnas.0606884104
|View full text |Cite
|
Sign up to set email alerts
|

Prokineticin receptor 2 (Prokr2) is essential for the regulation of circadian behavior by the suprachiasmatic nuclei

Abstract: The suprachiasmatic nucleus (SCN), the brain's principal circadian pacemaker, coordinates adaptive daily cycles of behavior and physiology, including the rhythm of sleep and wakefulness. The cellular mechanism sustaining SCN circadian timing is well characterized, but the neurochemical pathways by which SCN neurons coordinate circadian behaviors remain unknown. SCN transplant studies suggest a role for (unidentified) secreted factors, and one potential candidate is the SCN neuropeptide prokineticin 2 (Prok2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
142
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(150 citation statements)
references
References 30 publications
8
142
0
Order By: Relevance
“…This is consistent with the notion that not only does the SCN control the timing of sleep, but that there is also a mechanism whereby sleep states provide feedback that influences SCN activity (Deboer et al, 2003). The most dramatic effect of Alprazolam was seen with mProk2, which acts via the Prok2 receptor to coordinate circadian behavior and physiology (Li et al, 2006;Prosser et al, 2007). The impaired expression of mProk2 in SCN from R6/2 mice offers a potential cause of the disturbed circadian behavior in these mice.…”
Section: Discussionsupporting
confidence: 73%
“…This is consistent with the notion that not only does the SCN control the timing of sleep, but that there is also a mechanism whereby sleep states provide feedback that influences SCN activity (Deboer et al, 2003). The most dramatic effect of Alprazolam was seen with mProk2, which acts via the Prok2 receptor to coordinate circadian behavior and physiology (Li et al, 2006;Prosser et al, 2007). The impaired expression of mProk2 in SCN from R6/2 mice offers a potential cause of the disturbed circadian behavior in these mice.…”
Section: Discussionsupporting
confidence: 73%
“…Similar dim red light illumination is commonly used for monitoring locomotor activity in circadian studies (e.g. [4,5,7,[24][25][26]). We monitored locomotor activity and analysed circadian rhythms with the CLOCKLAB data acquisition and analysis system (Actimetrics Co., Wilmette, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…A screen for secreted factors of the suprachiasmatic nucleus (Kramer et al 2005) has identified transforming growth factor-a and the neuropeptide cardiotrophin-like cytokine (Kraves & Weitz 2006) as likely mediators of SCN output. More recently, loss of the genes encoding either the SCN peptide prokineticin 2 (Prok2; Li et al 2006, Hu et al 2007 or its cognate receptor Prok2R (Prosser et al 2007) has been shown to compromise circadian endocrine, behavioural and thermoregulatory rhythms, with particular effects in early night. Moreover, homeostatic regulation of sleep is compromised in mice lacking the Prok2 gene.…”
Section: Real-time Imaging Of the Scn Circadian Circuitrymentioning
confidence: 99%